Human Resource Aspect in the Medium-Term National Action Agenda for Productivity (MNAAP) - Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2000)
Berhman (1990) cited the Philippines as one of the few countries where the otherwise well accepted positive relationship between human capital investments and economic growth seems to fail. This reveals a lot about the link between productivity and skill production in this country. This paper reviews the issues and research gaps in the human resource dimension of the productivity puzzle. After reviewing the main issues in this area, the paper proceeded with augmenting the list of research issues and gaps identified in the human resource portion of the MNAAP strategy paper with other research issues and gaps.
Keywords: 330; productivity; human resource development; Humankapital; Produktivität; Philippinen